El estudio psiquiátrico del infractor y su importancia en el contexto del proceso penal. - Macas Saritama, Rolando (2011)
The importance and transcendency of the titled partner-juridical problem; "The Offender's Psychiatric Study and their Importance in the Context of the Penal Process", it is based mainly in the necessity of guaranteeing the rehabilitation and readaptation from the mental sick person to the society, through a specialized and suitable gratuitous treatment in Hospitals Psychiatric Publics that offer this help to people that are inmersas in crimes and that for their psychiatric illness boarding schools should remain in the Centers of Social Rehabilitation of the country, for not being accepted in the psychiatric hospitals when being considered dangerous for the other ones patient, therefore the State owes a criminal politics it dictates in charge of guaranteeing the human rights of all the private people of its freedom in the prison centers, particularly the right to the mental health of the sick persons psychiatric offenders. When investigating this topic, encounter that a normative one doesn't exist concrete in the Ecuadorian penal régime that guarantees the measures of security post-delictual with a rehabilitation treatment to be applied the mental sick persons that attempt against the life of people, that makes necessary to present an artificial proposal in having walked to incorporate future reformations to the penal, previous régime it is necessary to avoid the indefinite confinamiento of the sick persons psychiatric offenders; that we find it in the jails without receiving rehabilitative treatment some. The theoretical work and of field of the present thesis it allowed me to obtain approaches, with clear and precise foundations, of very grateful bibliography that you/they contributed to the verification of objectives, and contrastación of the outlined hypothesis, allowing to support the proposed changes. The content of the thesis is the author's intellectual effort in the scientific and methodological environment that approaches theoretical and empirically, the limitation to the fundamental right of the rehabilitation of all person considered inimputable; and that it is interned in a Prison Center by judicial ordinance, for not being received in the psychiatric hospitals of the country that are institutions with ends of lucre, and they don't help social and professionally to the inimputable that belong to the group of high-priority attention.